THE COMPARISON OF BLOCK LEARNING WITH TRADITIONAL LEARNING IN DEVELOPING THREE COMPETENCY ASPECTS OF MECHANICAL ENGINEERING STUDENTS - Widarto, Widarto; Jarwopuspito, Jarwopuspito; Rahdiyanta, Dwi; Wibowo, Aris Eko; Djati, Unaga Indera (Department of Mechanical Engineering Education, 2024)
Three aspects of student competency consisting of knowledge (cognitive), skills (psychomotor), and attitude (affective). This study aims to compare the achievement of basic machining competencies in block system learning and traditional learning. This study used a quantitative descriptive approach. The method was a quasi-experimental method with posttest only control group design, with the block system treatment in the experimental group and the traditional or regular learning in the control group. The experimental group consisted of 75 students from the Applied Bachelor Degree of Mechanical Engineering Study Program (Diploma 4), and the control group consisted of 66 students from the Bachelor Degree of Mechanical Engineering Education Study Program as the control group. Research data was obtained from the post-test scores for the Machining Theory course and the final scores for Basic Machining Practices. Descriptive statistics show that students' competency achievements in the knowledge aspect in block learning are less good than in traditional learning. However, student competency achievements in the skills and attitude aspects in the block learning system are better than in traditional learning. Although further statistical tests are needed to measure the differences and significance between the two learning modes, these results have provided an illustration of the weaknesses of block learning in theoretical and conceptual learning. Therefore, educators need to apply innovative learning strategies to overcome these weaknesses.